(untitled) (Research, Society and Development, 2021)
Sialolithiasis is a common disease that affects the major salivary glands and can occur at any age. Parotid glands are rarely involved and, even rarer are the cases of sialoliths larger than 10 mm. This report presents the rare case of a giant parotid sialolith associated with facial cellulitis in a 75-year-old man. The treatment involved initially non-surgical approach followed by a minimally invasive surgery to restore health and function. The treatment protocol was completely successful and proved effective in clinical and surgical management of giant parotid sialolith associated with facial cellulitis.